(untitled) (Swiss Medical Weekly, 2013)
OBJECTIVE: To evaluate the patient characteristics and natural history of pubic rami fractures in geriatric patients, with a special focus on the frequency of concomitant posterior pelvic ring lesions and the percentage of secondarily operated patients as a result of conservative treatment failure. STUDY DESIGN: Retrospective cohort study. Patients were treated in a university hospital that is equivalent to a level I Trauma centre. PATIENTS AND METHODS: We analysed 132 consecutive patients (113 women, 19 men), >65 years old, presenting with low energy-trauma pubic rami fractures at our emergency department from January 2009 to December 2011. RESULTS: Mean age of patients was 84 years (range 66–100). Women were affected six times more frequently than men. Almost 30% of patients lost their previous independence permanently owing to the injury. Ninety eight percent of previously independent patients (community dwellers) required temporary hospital care for a median duration of 39 days (interquartile range [IQR] 28–52). One-year mortality was 18.5%. A concomitant posterior pelvic ring lesion was identified by computed tomography in 54% of patients. In 4% of the patients secondary operative fracture stabilisation was performed. DISCUSSION: Pubic rami fractures are frequently associated with concomitant posterior pelvic ring injuries, making these injuries more unstable than generally assumed. Based on this fact and the long duration of hospital stay, more aggressive management of these injuries may be considered. The principle aims in this patient population are satisfying pain management, early mobilisation, conservation of independence and return to previous place of residence.